Transforming growth factor beta 1 induced endothelin-1 release is peroxisome proliferator-activated receptor gamma dependent in A549 cells. Issue 1 (December 2016) - Xiang, Shulin; Zeng, Yi; Xiong, Bin; Qin, Yueqiu; Huang, Xia; Jiang, Yujie; Luo, Weigui; Sooranna, Suren; Pinhu, Liao
Abstract Background Endothelin-1 (ET-1) is involved in pulmonary vascular remodeling. The aim of this study was to investigate the biochemical interactions between PPAR-γ, TGF-β1 and ET-1 in vitro. Methods A549 cells were pre-treated with S2505 (10 μM), S2871 (10 μM) with/without SB203580 (10 μM) for 60 min following 2 h treatment with 10 ng/mL TGF-β1. A549 cells were also transfected with positive or negative PPAR-γ plasmids for comparison. RT-PCR, ELISA, western blotting and confocal laser scanning microscopy (CLSM) were used to measure the relevant expression of mRNA, protein, mediators of pathways and nuclear factor translocation. Results SB203580 inhibited TGF-β1 induced ET-1 expression in A549 cells. S2871 decreased PPAR-γ mRNA and increase TGF-β1-induced ET-1 expression. S2871 increased phosphorylation of p38 MAPK and Smad2. Cells transfected with PPAR-γ negative plasmid increased TGF-β1 induced ET-1 expression, and increased the expression of phospho-p38 MAPK and phospho-Smad2. S2505 increased PPAR-γ mRNA expression, suppressed the increased TGF-β1-induced expression of ET-1. S2505 inhibited TGF-β1 induced phosphorylation of p38 MAPK and Smad2, also the nuclear translocation of Smad2. Cells transfected with PPAR-γ positive plasmid reduced TGF-β1-induced ET-1 expression, and inhibited the expression of phospho-p38 MAPK and phospho-Smad2. Conclusions TGF-β1 induced release of endothelin-1 is PPAR-γ dependent in cultured A549 cells.